28.3k views
0 votes
Can anyone show me how I would figure this problem out

Can anyone show me how I would figure this problem out-example-1

2 Answers

6 votes

Answer:

11

Explanation:

it means if x =< -4 do

h(x) = - 0.5x - 15

else if x > -4 do

h(x) = 20 - 3x^2

so from the question we need to find the value of h(-4) + 3h(-2)


h(-4) + 3h(-2) = ( - 0.5 * ( -4 ) - 15 ) + 3( 20 - 3( -2 )^2 )

= ( -13 ) + 24 = 11

User Gseattle
by
5.8k points
5 votes

The value of x is the number inside the parenthesis, so h(-4) gives x a value of -4.

The equation says when X is ≤ -4 use the first equation


So h(-4) = -1/2(x) -15

= -1/2(-4) -15

= 2 -15

= -13


When x = -2 (h(-2) ) use the 2nd equation:

h(-2) = 20-3x^2

=20-3(-2)^2

= 20-3(4)

=20-12

=8


Now you have -13 + 3(8)

= -13 + 24

=11


The answer should be 11

User PavKR
by
5.4k points